Designing Core‐Shell Ni(OH)2@CuO Nanowire Arrays on 3D Copper Foams for High‐Performance Asymmetric Supercapacitors. Issue 21 (8th November 2019) - Xu, Li'na; Zhang, Hua; Li, Jiao; Guo, Xue; Sun, Haibin; Li, Yan'an; Wu, Tong
Abstract: Core‐shell Ni(OH)2 @CuO electrodes grown on three‐dimensional copper foams were synthesized by a facile thermal oxidation and chemical bath deposition method. The electrochemical experiments present that the Ni(OH)2 @CuO electrode delivers large areal capacitance (1.625 F cm −2 at 3 mA cm −2 ), excellent rate capacity (1.285 F cm −2 at 30 mA cm −2 ), and brilliant cycling stability (retaining 96.4 % after 5000 cycles). In addition, an asymmetric supercapacitor (ASC) device was designed taking Ni(OH)2 @CuO electrode and active carbon (AC) as a positive and negative electrode, respectively. The ACS device exhibits a high voltage of 1.6 V and remarkable energy density up to 58.59 Wh kg −1 at a power density of 686.45 W kg −1 . This work may serve to develop new areas of low‐cost materials for energy storage and conversion system. Abstract : A fine design : Hierarchical core/shell‐like Ni(OH)2 @CuO electrode composites with large capacitance are synthesized by a facile two‐step in situ oxidation reaction and chemical bath deposition method. The Ni(OH)2 @CuO electrode composites composite synthesized exhibits a high specific capacitance of 1.625 F cm −2, long cycle life with capacitance retention of 95.6 % after 5000 cycles, high energy density of 58.59 Wh kg −1 at a power density of 686.45 W kg −1 .